Postnatal Maturation of the Glomerular Filtration Rate in Conventional Growing Piglets As Potential Juvenile Animal Model for Preclinical Pharmaceutical Research - Gasthuys, Elke; Devreese, Mathias; Millecam, Joske; Sys, Stanislas; Vanderperren, Katrien; Delanghe, Joris; Vande Walle, Johan; Heyndrickx, Marjolein; Croubels, Siska (Frontiers in Pharmacology, 2017)
Adequate animal models are required to study the preclinical pharmacokinetics (PK), pharmacodynamics (PD) and safety of drugs in the pediatric subpopulation. Over the years, pigs were presented as a potential animal model, since they display a high degree of anatomical and physiological similarities with humans. To assess the suitability of piglets as a preclinical animal model for children, the ontogeny and maturation processes of several organ systems have to be unraveled and compared between both species. The kidneys play a pivotal role in the PK and PD of various drugs, therefore, the glomerular filtration rate (GFR) measured as clearance of endogenous creatinine (Jaffe and enzymatic assay) and exo-iohexol was determined in conventional piglets aging eight days (n = 16), four weeks (n = 8) and seven weeks (n = 16). The GFR data were normalized to bodyweight (BW), body surface area (BSA) and kidney weight (KW). Normalization to BSA and KW showed an increase in GFR from 46.57 to 100.92 mL/min/m² and 0.49 to 1.51 mL/min/g KW from eight days to seven weeks of age, respectively. Normalization to BW showed a less pronounced increase from 3.55 to 4.31 mL/min/kg. The postnatal development of the GFR was comparable with humans, rendering the piglet a convenient juvenile animal model for studying the PK, PD and safety of drugs in the pediatric subpopulation. Moreover, to facilitate the assessment of the GFR in growing piglets in subsequent studies, a formula was elaborated to estimate the GFR based on plasma creatinine and BW, namely eGFR = 1.879 x BW^1.092/PCr^0.600.